Peran Pemerintah Terhadap Keberlanjutan Usaha Arak Di Desa Datah, Kecamatan Abang, Kabupaten Karangasem - Ulaningsih, Ni Luh Trisna; Suwena, Kadek Rai (Universitas Pendidikan Ganesha, 2024)
The aim of this research is to determine the characteristics of arak producers and the role of the government in the bad intentions of the arak business in Datah Village, Abang District, Karangasem Regency. In this study, the sample size used the Slovin formula, a total of 73 people. The sampling technique uses probability sampling techniques by providing equal opportunities for each member of the population to be selected as a member of the sample. The type of data used in this study is quantitative data in the form of answers to questionnaire questions with a Likert scale. This research uses primary data and secondary data. The data collection method uses questionnaires and interviews. The data analysis technique used is simple linear regression analysis. The results showed that (1) the characteristics of respondents of arak entrepreneurs in Datah Village, Abang District, Karangasem Regency, the majority were men with the age of >45 years and high school/vocational education. (2) The role of the government has a positive and significant influence on the sustainability of the arak business in Datah Village, Abang District, Karangasem Regency.